Analysis of factors influencing digital financial literacy levels: a case study on gen Y and gen Z spending behavior - Murviana Koto (International Journal Reglement & Society (IJRS), 2023)
This study aims to estimate and analyze the relationship between variables using quantitative data. The data presented is cross section data, the data studied is more than one. The variables that will be observed are the variables that determine the buying behavior of Gen Z and Millennials. This type of research is survey research, because it takes samples from one population. This study uses an explanatory research approach. The approach used is a quantitative description.. This research aims to look at the Factors Influencing the Level of Digital Financial Literacy based on shopping behavior. The population in this study are adolescents aged 10-19 years (Gen Z) and those aged 20-37 years (Gen Y) who shop online with e-commerce in Medan City. The purpose of this study is to look at the differences in shopping behavior of Gen Z and Gen Y. Since there is no data on young people who shop online using e-commerce (the number is unknown), the sample selection framework is non-probability sampling. The method used is purposive sampling, especially quota sampling. This method is used to ensure that the various subgroups in the population are represented with various sample characteristics to a certain extent as desired by the researcher. The samples taken were respondents from Gen Z and Gen Y who shopped online using e-commerce which were randomly selected.